Effect of selected lifestyle factors on the nutrition state of elderly people with metabolic syndrome - Lucyna Pachocka; Tomasz Chmielewski; Irena Stolarska (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. The formation and development of the metabolic syndrome (MetS) is largely caused by lifestyle factors. Many studies have shown that excessive consumption of simple carbohydrates, alcohol, salt, physical inactivity and smoking increase the risk of MetS. Objective. The aim of the study was to assess the nutritional status and its relationship with selected lifestyle factors in elderly people with MetS. Material and methods. 81 people aged 51-75 participated in the study. According to the guidelines, all tests were performed on an empty stomach. The comparison of individual quantitative variables between the groups was performed using the Student's t-test for independent measurements or using the Mann-Whitney U test. The relationship between quantitative variables was verified with the Spearman's correlation coefficient. All statistical tests were based on a significance level of p<0.05. Results. The BMI, the percentage of body fat and the waist circumference significantly exceed the norm for the population in the examined persons. The responses of respondents aged 51-65 show that 36% of people sweetened their drinks, 65.6% were salted their food, 51.6% consumed alcohol, and at the age of 66-75, respectively: 47.1%, 52.9%, 41.2%. There was no correlation between sweetening beverages and salting food and the concentration of glucose and lipids. However, a positive correlation was found between the amount of salt consumed and the heart rate (r=0.28, p<0.05). In both age groups, statistically significant differences in the concentration of triglycerides depending on alcohol consumption or non-consumption were found. Due to the lack of precise data on the amount of alcohol consumed, the correlation between alcohol consumption and the concentration of glucose and lipids was not analyzed. Physical activity was not undertaken by 39.1% of patients aged 51-65 years and 41.2% of patients aged 66-75 years. In the group of elderly people without physical activity, a statistically significantly higher glucose concentration was found in relation to those who were physically active (130 mg/dl vs. 105 mg/dl; p=0.031). Patients aged 51-65 who engaged physical activity had statistically significantly lower body weight, BMI, waist circumference and lean body mass, which requires further studies. Conclusions. The anthropometric indices and parameters of MetS patients indicated disturbances in the nutritional status. Unhealthy lifestyle was shown mainly in the younger group of patients 51-65 years old (they sweetened drinks more often, salted dishes, consumed alcohol). Patients with metabolic syndrome did not undertake physical activity as often as recommended.